World art 2 [videorecording (DVD)] - Lynn, Cherie (Jumby Bay Studios, 2005)
Instructor Cherie Lynn demonstrates art projects from 11 different cultures in easy to understand, step-by-step instructions. Featured cultures include the Navajo Indians, the False Face Society, the Tibetan Mandalas, and many more.